Oil Boomtowns - Christy Davis (Symphony in the Flint Hills, 2014)
Butler and Greenwood Counties were both organized in 1855. But they would have to wait more than a half century to realize the promise of illustrious place names like “El Dorado” and “Prospect Township.” When World War I raised the demand for oil, prices spiked and investors came calling on area farmers and ranchers, who quickly learned that oil was a “better crop than alfalfa.”
Keywords: oil; history; Butler county; El Dorado; Barlesville; sand; working; rubberneck; barrels; Greenwood County; Teterville; Cassoday; Kansas Oil Museum; boomtown; gas; Oil Hill; Midian; Haskin; Thrall; Kenbro; Birkett; Sallyards; Oil Capital of Kansas; John Stapleton